Nighttime sleep, its disturbances, and subjective assessment in patients with essential arterial hypertension - N. S. N.S. Pegova (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To investigate nighttime sleep disturbances in patients with essential arterial hypertension (EAH) and possible effects of these disturbances on EAH clinical course.Material and methods. In total, 98 patients with Stage I-II EAH were examined. All participants underwent standard clinical examination, 24-hour blood pressure monitoring (BPM), questionnaire survey on nighttime sleep disturbances, and time deficit level measurement.Results. EAH patients were characterized by frequent intrasomnic and presomnic disturbances, such as difficulty falling asleep, frequent night awakening, snoring, and superficial sleep. Fifty per cent of the patients regarded general quality of their sleep as "good", 35,71 % - as "fair", 10,20 % - as "bad", and only 4,08 % - as "very good". A group of EAH patients was identified, characterised by severe nighttime sleep disorders, elevated anxiety level, and disturbed circadian BP profile (non-dippers, night-peakers).Conclusion. EAH patients often suffered from somnologic disturbances, which progressed with longer duration and more severe clinical course of the disease. For early EAH stages, intra- and presomnic disturbances were typical, with further development of general sleep structure disorders.